Production of ornamental sunflower irrigated with oilfield produced water in the Brazilian semiarid region - Weber, Olmar Baller; Crisostomo, Lindbergue Araújo; Miranda, Fabio Rodrigues de; Sousa, Adervan Fernandes; Mesquita, Antônio Lindemberg Martins; Cabral, José Ednilson de Oliveira (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effects of irrigation with oilfield produced water on the concentration of some soil nutrients, as well as on the performance and concentration of nutrients in the roots and on aerial parts of the ornamental sunflower 'Sunbright' (Helianthus annuus), and to define the operating costs for the production of floral stems under an irrigated system. 'Sunbright' sunflower plants were cultivated in a Typic Quartzipsamment in the state of Ceará, Brazil, and subjected to drip irrigation treatments with oilfield produced water treated by filtration (PWF), or by reverse osmosis (PWO), besides a control treatment with groundwater (GW) from the Açu aquifer. The study was carried out for three successive production cycles. Irrigation with PWF modifies the concentration of exchangeable salts in the soil, increasing Na+ in the shallow layers, affecting the vegetative growth and the nutrient accumulation in the roots and shoots, in such a way that brackish water may impact operating costs and revenues in the production of floral stems. PWO has a minor effect on soil nutrients and it is not able to modify the agronomic performance of the ornamental sunflowers, in comparison with irrigation with GW. The cost-benefit ratio was positive with all types of water in the following order: GW> PWF> PWO.